Tradução para o português e validação do questionário de interpretação da neuropatia pelo paciente (PIN) - Matos, Mozânia Reis de (2015)
In practical prevention , the instruments that extend self-care are welcome. Added to this the stimulus promotion, health education and the interdisciplinary care. The Patient Interpretation of Neuropaty (PIN), is a questionnaire of Interpretation of neuropathy by patient, developed and validated in the USA and in England (UK). By means of this instrument, the patient makes the self-evaluation of your foot and health care to be carried out with it, aiming at the prevention of ulcer diabetic foot. Thus, the aim of the present study is to translate and validate the questionnaire of interpretation of neuropathy for the Portuguese and assess the degree of understanding of the patients on the questions of (PIN). Participated in this study 100 patients at the outpatient clinic of foot insensitive of the Institute of Orthopedics and Traumatology, University of Sao Paulo. Were used parametric and non-parametric tests in the analysis of data.The values obtainedwith the BrazilianversionPINare verysimilar to the valuesof the original versions, theUSAandtheUK.We think it isa valuabletool providingthe patientobserveneuropathicchangesthat increase the risk of ulcers on the feet. The questionnairetranslated and validatedfor the Portuguese language, soit seemsto be a reliableandapplicabletool to evaluate theself-careof the patientat the same timethat allows thehealthcare professionalto designeffective measuresforprevention ofdiabetic footulcer, resulting in a betterprognosisandquality of life ofdiabetes patientswithND.